ANTECEDENTS CUSTOMER DELIGHT AND CONSEQUENCES IT (Study on Padang Restaurants and Sundanese Restaurants in Jakarta) - Nonot Yuliantoro; Ferdi Antonio (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Urban people have a lifestyle of enjoying culinary as a tourist activity and sharing their dining experiences through social media. The purpose of this study was to determine whether 1) Perception of food authenticity, 2) Servicescape, 3) Service encounters affect local food experience, 4) Local food experience affects customer satisfaction, 5) Customer satisfaction affects 6) Revisit Intention and 7) Willingness to post and share photos to social media. This research method is a quantitative survey with an online questionnaire instrument with a purposive sampling technique to millennial consumers between 24 and 40 years old who live in Jakarta and surrounding areas in October 2021. The number of samples used is 160 and data analysis uses a Partial Least Square approach. -structural equation modelling using smart software pls 3.29. The results of this study indicate that there is an influence between the perception of food authenticity on the local food experience, there is an influence between the service atmosphere on the local food experience, there is an influence between the local food experience on customer satisfaction, there is an influence of customer satisfaction on the intention to return, as well as there is an influence customer satisfaction with the willingness to post and share photos on social media. However, there is no relationship between service encounters and local food experience.